Miller–Payne Grading and 70-Gene Signature Are Associated With Prognosis of Hormone Receptor-Positive, Human Epidermal Growth Factor Receptor 2-Negative Early-Stage Breast Cancer After Neoadjuvant Chemotherapy - Wang, Liye; Luo, Rongzhen; Lu, Qianyi; Jiang, Kuikui; Hong, Ruoxi; Lee, Kaping; Zhang, Ping; Zhou, Danyang; Wang, Shusen; Xu, Fei (Frontiers in Oncology, 2021)
Background: HR+/HER2- breast cancer (BC) has a much lower pathological complete response (pCR) rate to neoadjuvant chemotherapy (NAC). Therefore, to better stratify the relapse risk for HR+/HER2- non-pCR populations, it's essential to accurate identification new prognostic markers. Methods: The study retrospectively analyzed 105 stage II-III patients who were diagnosed with HR+/HER2- BC and received NAC followed by breast and axilla surgery between 2013 and 2019 in Sun Yat-Sen University Cancer Center. The Miller-Payne (MP) grading system was used to evaluate pathological responses to NAC. The 70-gene signature was used to classify the prognosis-signatures. Results: Among 105 patients, the study demonstrated that larger tumor size and lower progesterone receptor level at baseline, larger tumor size of postoperative were statistically significantly associated with worse disease-free survival (DFS) (p = 0.004, p = 0.021 and p = 0.001, respectively). Among 54 patients who underwent the 70-gene assays, 26 (48.1%) had a low risk-signature, 28 (51.9%) patients had a high risk-signature. Patients with poor response (MP Grades 1-2) were more likely to with a high risk 70-gene signature than those with good response (MP Grades 4-5). The final analysis showed that DFS was longer in the Low-risk group than in the High-risk group (52.4 months vs. 36.1 months of the median DFS, hazard ratio (HR) for recurrence, 0.29; 95% confidence interval (CI), 0.10 to 0.80; p = 0.018). DFS was longer in the good response (MP grades 3-4) group than in the poor response (MP grades 1-2) group (94.7% vs. 60% of the patients free from recurrence; HR: 0.16; 95% CI: 0.05 to 0.47; p = 0.037). When stratified by MP grades combined with the 70-gene signature, subgroup analyses showed the good response-low risk group with the best DFS, whereas the poor response-high risk group showed the worst DFS (p = 0.048). Due to the short median follow-up time was 34.5 months (5.9-75.1 months), MP grades and the 70-gene signature did not show significant prognostic value for overall survival. Conclusions: The study showed that analysis of MP grades combined with the 70-gene signature with residual NAC-resistant breast samples has a significant correlation with DFS.